T THE RELATIONSHIP BETWEEN STROKE CLASSIFICATION AND IMPAIRED COGNITIVE FUNCTION IN STROKE PATIENTS - Dewi Nopia; Zaqyyah Huzaifah (Journal of Nursing Invention)
Background: Stroke is the second leading cause of death in the world. Stroke is a vascular disorder caused by blockage or rupture of blood vessels in the brain, resulting in a clinical disorder due to damage to brain cells in certain parts. Symptoms can disrupt the process of mental activity or sublime cortilal function including cognitive function. Objective: This study aims to determine the relationship between stroke classification and impaired cognitive function in stroke patients. Methods: This study uses a correlation analysis method, with a cross-sectional design, a sample of 36 respondents according to the criteria, using Chi Square at α = 0.05.